The Use of Mingle Game to Improve the Students’ Speaking Skill at Grade XI SMK Negeri 1 Gunungsitoli in 2022/2023 - Fatiaro Daeli; Yaredi Waruwu; Kristof M,E Telaumbanua; Trisman Harefa (Departement of Mathematics Education, 2023)
Speaking is one of the most skills that people should dominate to create communication between humans. To improve the students’ speaking skill by using of Mingle Game of the eleventh grade SMK Negeri 1 gunungsitoli which the total numbers of the students was 30 persons. The research was conducted by using Classroom Action Research (CAR) design. This research was applied into two cycles. Each cycle consisted of planning, action, observation, and reflection. The instruments used by the researcher to collect the data were observation sheet, evaluation sheet and field note. From the result of each Cycle, the researcher finds that the students get an improve the students’ speaking skill by using of Mingle Game. In the second meeting of cycle II, the researcher obtained the improvement of students, who achieved the Minimum Competence Criterion (70). There were 1 (7%) student who got score among 75-100 classified as “Very Good Criteria”, 29 (93%) students got score among 75-84 classified as “Good Criteria”. In Cycle II the highest mark was 95 and the lowest was 65. Based on the result above the researcher concludes that The Use of Mingle Game could be done Improve the Students’ Speaking skill.